A copper-manganese bimetallic oxide positive electrode material and its preparation method and application

By using the core-shell structure of the copper-manganese bimetal oxide positive electrode material in aqueous zinc ion batteries, the problems of low capacity and poor circulation performance of manganese-based materials are solved, and high specific capacity and stable charge and discharge cycle performance are achieved.

CN119008917BActive Publication Date: 2025-01-10XIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411420434.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing manganese-based positive electrode materials have problems with low capacity and poor charge and discharge cycle performance in aqueous zinc ion batteries.

Method used

The copper-manganese bimetal oxide positive electrode material is used, which is a core-shell structure, including the CuxO core and the coated MnO2 shell, and is prepared by solvent-thermal reaction and hydrothermal reaction. The molar ratio of Cu to Mn is (9:1)~ (1:9), forming a core-shell structure to improve conductivity and reaction kinetics.

Benefits of technology

Improve the specific capacity and charge and discharge cycle stability of the positive electrode material, enhance the contact area between the electrode and the electrolyte interface, provide more redox active sites, promote the valence of manganese active sites and the kinetics of electrochemical reactions, and significantly improve the Discharge specific capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119008917B_ABST
    Figure CN119008917B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of positive electrode materials for aqueous zinc ion secondary batteries, and discloses a copper-manganese bimetallic oxide positive electrode material and a preparation method and application thereof. The copper-manganese bimetallic oxide positive electrode material includes Cu x O core, and the Cu coated x O-core MnO 2 Shell; wherein 1<x<2. In this application, Cu x O introduced into MnO 2 system, forming an electrochemically active core-shell two-phase structure, in which the shell MnO 2 Nanosheets grown in situ on Cu x O nanosphere core surface, during the electrochemical reaction, has a conductive Cu x O core promotes H + and Zn 2+ In MnO 2 The insertion and deinsertion in the electrochemical reaction can improve the electrochemical reaction kinetics; while MnO 2 Nanosheets coated with Cu x O core, buffering and inhibiting Cu x The volume expansion and pulverization caused by the O phase conversion reaction improve the specific capacity and charge-discharge cycle stability of the electrode material through the synergistic effect of the core-shell two phases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of positive electrode materials for aqueous zinc ion secondary batteries, and in particular to a copper-manganese bimetallic oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density and long cycle life and are widely used in various fields. However, the lithium salt organic electrolyte used in lithium-ion batteries has the hidden danger of being flammable and explosive during use; and the lithium, cobalt and nickel resources used in lithium-ion batteries are scarce, resulting in high manufacturing costs. Safe, stable, easy to manufacture and low-cost secondary batteries are what people pursue.

[0003] Aqueous zinc-ion batteries (AZIBs) are secondary batteries based on the migration and insertion / extraction reaction of zinc ions in aqueous solution. They use zinc as the negative electrode, manganese-based compounds as the positive electrode, and an aqueous solution of zinc salts and manganese salts as the electrolyte. The zinc and manganese resources used in secondary aqueous zinc-ion batteries are abundant and can be encapsulated in the natural environment, enabling large-scale low-cost manufacturing. They are suitable for low-cost energy storage markets such as electric two-wheelers, as well as large-scale static energy storage scenarios of renewable energy, such as intermittent clean energy storage such as solar energy, wind energy, and tidal energy.

[0004] As an important component of aqueous zinc-ion batteries, cathode materials directly affect the overall performance of batteries. Among many materials, manganese-based cathode materials have attracted extensive attention from researchers due to their low toxicity and abundant resources. However, manganese-based cathode materials have some problems, such as poor conductivity, Zn 2+ The slow diffusion kinetics and the accompanying dissolution of electrode materials during the cycle process limit the development of aqueous zinc-ion batteries.

[0005] Developing manganese-based positive electrode materials with high specific capacity and good charge-discharge cycle performance is the key to obtaining high-performance aqueous zinc-ion secondary batteries. Summary of the invention

[0006] The present application provides a copper-manganese bimetallic oxide positive electrode material and a preparation method and application thereof, aiming to solve the problems of low capacity and poor charge-discharge cycle performance of existing manganese-based positive electrode materials.

[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0008] In a first aspect of the present application, a copper-manganese bimetallic oxide positive electrode material is provided, which is a core-shell structure, including Cu x O core and the Cu coated x O core with a MnO2 shell; wherein 1<x<2.

[0009] Preferably, in the copper-manganese bimetallic oxide positive electrode material, the molar ratio of Cu to Mn is (9:1) to (1:9).

[0010] The second aspect of the present application provides a method for preparing the copper-manganese bimetallic oxide positive electrode material, comprising:

[0011] S1, dissolving copper salt, surfactant and reducing agent in a solvent, mixing them evenly and then performing a solvothermal reaction, collecting the solid phase product in the reaction solution, washing and drying, and obtaining a precursor Cu2O;

[0012] S2, adding the precursors Cu2O, manganese salt and KMnO4 into deionized water for hydrothermal reaction, collecting the solid phase product in the reaction solution, washing and drying, and obtaining a copper-manganese bimetallic oxide positive electrode material with a core-shell structure.

[0013] Preferably, the molar ratio of copper salt, surfactant and reducing agent is 2.1:2:0.74.

[0014] Preferably, the ratio of the molar number of Cu in the precursor Cu2O to the sum of the molar number of Mn in the manganese salt and KMnO4 is (9:1) to (1:9);

[0015] The ratio of the molar number of Mn in the manganese salt to the molar number of Mn in KMnO4 is 1.6:1.

[0016] Preferably, in step S1, the temperature of the solvothermal reaction is 70°C to 90°C;

[0017] In step S2, the temperature of the hydrothermal reaction is 140°C to 160°C, and the reaction time is 10 to 14 h.

[0018] Preferably, the copper salt is at least one of copper sulfate, copper acetate or copper chloride;

[0019] and / or:

[0020] The surfactant is at least one of polyvinyl pyrrolidone, sodium lauryl sulfate or hexadecyl trimethyl ammonium bromide;

[0021] and / or:

[0022] The reducing agent is sodium borohydride or hydrazine hydrate;

[0023] and / or:

[0024] The manganese salt is at least one of manganese sulfate, manganese nitrate, manganese carbonate or manganese chloride;

[0025] and / or:

[0026] The solvent is dimethylformamide.

[0027] The third aspect of the present application provides the use of the above copper-manganese bimetallic oxide positive electrode material or the copper-manganese bimetallic oxide positive electrode material prepared by the above preparation method in a zinc ion battery.

[0028] In a fourth aspect of the present application, there is provided an aqueous zinc ion secondary battery positive electrode, comprising a current collector and a positive electrode material coated on the current collector;

[0029] The positive electrode material is formed by mixing the copper-manganese bimetallic oxide positive electrode material, a conductive agent and a binder.

[0030] In a fifth aspect of the present application, an aqueous zinc ion secondary battery is provided, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises the above-mentioned copper-manganese bimetallic oxide positive electrode material.

[0031] Compared with the prior art, the beneficial effects of this application are:

[0032] The copper-manganese bimetallic oxide positive electrode material of the present application is Cu x O is introduced into the MnO2 system to form a core-shell structure, and MnO2 nanosheets are in situ grown on Cu x O microsphere surface. Cu x The conductivity of O microspheres improves the reaction kinetics of MnO2 and provides sites for the deposition reaction of Mn, increasing the contact area between the electrode and the electrolyte interface. At the same time, the rough surface of the core-shell structure can provide more redox active sites, which is beneficial to the electrolyte ion Zn 2+ The MnO2 nanosheets coated with Cu2O2 can provide additional capacity and further improve the discharge capacity of the positive electrode material. x O core, buffered Cu x The volume expansion caused by the O phase transformation reaction gathers Cu x O core, inhibiting the expansion and pulverization caused by the phase conversion reaction. The synergistic effect of the core-shell two-phase structure improves the specific capacity and charge-discharge cycle stability of the positive electrode material.

[0033] The copper-manganese oxide obtained during the electrochemical reaction of the copper-manganese bimetallic oxide positive electrode material of the present application has stable and reversible electrochemical properties, and can give the positive electrode stable charge and discharge cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 Cu 1.66 Cyclic voltammetry curve of the full battery assembled with the positive electrode prepared by O@MnO2(4:6);

[0036] Figure 2 Cu 1.66 The charge and discharge curves of the full battery assembled with the positive electrode prepared by O@MnO2(4:6);

[0037] Figure 3 Cu 1.66 Rate capacity and coulombic efficiency of full batteries assembled with cathodes prepared with O@MnO2(4:6), Cu2O, and MnO2;

[0038] Figure 4 Cu 1.66 The charge and discharge cycle performance diagram of the full battery assembled with positive electrodes prepared by O@MnO2(4:6), Cu2O, and MnO2;

[0039] Figure 5 Cu 1.66 SEM images of O@MnO2(4:6), Cu2O, and MnO2;

[0040] Figure 6 Cu 1.66 TEM image of O@MnO2(4:6);

[0041] Figure 7 Cu 1.66 XRD patterns of O@MnO2(4:6), Cu2O, and MnO2;

[0042] Figure 8 Cu 1.66 XPS graphs of O@MnO2(4:6), Cu2O, and MnO2. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0044] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0045] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0046] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0047] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0048] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0049] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0050] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0051] In a first aspect, the present application provides a copper-manganese bimetallic oxide positive electrode material having a core-shell structure, comprising Cu x O core, and the Cu coated x O core MnO2 shell; since Cu exists in both Ⅰ and Ⅱ valence in the system, 1<x<2 in this application. The core-shell structure copper-manganese bimetallic oxide positive electrode material of this application is recorded as Cu x O@MnO2.

[0052] In the copper-manganese bimetallic oxide positive electrode material, the molar ratio of Cu to Mn is (9:1) to (1:9), such as 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9 or any ratio within this range.

[0053] The copper-manganese bimetallic oxide positive electrode material of the present application is Cu x O was introduced into the MnO2 system, and MnO2 nanosheets were in situ grown on Cu x O microspheres are deposited on the surface to form a core-shell structure. The core-shell two-phase structure synergistically improves the specific capacity and charge-discharge cycle stability of the positive electrode material.

[0054] In the copper-manganese bimetallic oxide positive electrode material of the present application, Cu x The conductivity of O microspheres improves the reaction kinetics of MnO2 and provides sites for the deposition reaction of Mn, increasing the contact area between the electrode and the electrolyte interface; at the same time, the rough surface of the core-shell structure can provide more redox active sites, which is beneficial to the electrolyte ion Zn 2+ Insertion and shuttle into the active material promotes the valence change and electrochemical reaction kinetics of manganese active sites, and improves the rate capacity of the positive electrode material. In addition, Cu2O is electrochemically active and can provide additional capacity, further improving the discharge specific capacity of the positive electrode material.

[0055] In the copper-manganese bimetallic oxide positive electrode material of the present application, MnO2 nanosheets are coated with Cu x O core, buffered Cu x The volume expansion caused by the O phase transformation reaction gathers Cu x O core, inhibiting the expansion and powdering caused by phase inversion reaction.

[0056] The copper-manganese oxide obtained during the electrochemical reaction of the copper-manganese bimetallic oxide positive electrode material of the present application has stable and reversible electrochemical properties, and can give the positive electrode stable charge and discharge cycle performance.

[0057] In a second aspect, the present application provides a method for preparing the above copper-manganese bimetallic oxide positive electrode material, comprising:

[0058] S1, dissolving copper salt, surfactant and reducing agent in a solvent, mixing them evenly and then performing a solvothermal reaction, collecting the solid phase product in the reaction solution, washing and drying, and obtaining a precursor Cu2O;

[0059] Specifically, copper salt, surfactant and reducing agent are dissolved in a solvent, and a solvothermal reaction is carried out at 70°C-90°C. The reaction solution after the solvothermal reaction is filtered to collect the precipitate; the precipitate is washed with water 3 times and ethanol 2 times, and dried in an oven at 60°C for 12 hours to obtain a spherical precursor Cu2O. The solvent is preferably dimethylformamide; the molar ratio of copper salt, surfactant and reducing agent is preferably 2.1:2:0.74.

[0060] The copper salt can be any one of copper sulfate, copper acetate or copper chloride or a mixture of two or more thereof, preferably copper acetate.

[0061] The reducing agent is used to reduce divalent copper to monovalent copper; the reducing agent can be sodium borohydride or hydrazine hydrate, preferably sodium borohydride.

[0062] The surfactant is used to adjust the morphology of the spherical Cu2O; the surfactant can be selected from at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, and hexadecyl trimethyl ammonium bromide, preferably polyvinyl pyrrolidone.

[0063] S2, adding the precursors Cu2O, manganese salt and KMnO4 into deionized water for hydrothermal reaction, collecting the solid phase product in the reaction solution, washing and drying, and obtaining a copper-manganese bimetallic oxide positive electrode material with a core-shell structure.

[0064] Specifically, the precursors Cu2O, manganese salt and KMnO4 are added to deionized water, and a hydrothermal reaction is carried out at 140 ℃-160 ℃ for 10-14 h. The reaction solution is filtered to obtain a solid phase, which is washed with water three times and dried in an oven at 60 ℃ for 12 h to obtain a core-shell structured copper-manganese bimetallic oxide positive electrode material.

[0065] In the present application, the manganese salt can be at least one of manganese sulfate, manganese nitrate, manganese carbonate and manganese chloride, preferably manganese sulfate.

[0066] In the present application, a copper-manganese bimetallic oxide positive electrode material with a core-shell structure is formed by using a manganese salt in combination with KMnO4. The ratio of the molar number of Cu in the precursor Cu2O to the sum of the molar number of Mn in the manganese salt and KMnO4 is (9:1) to (1:9). Among them, KMnO4 can participate in the formation of MnO2, and Cu x O. In terms of the molar number of Mn, the molar ratio of manganese salt to KMnO4 is preferably 1.6: 1. Within this ratio range, a copper-manganese bimetallic oxide positive electrode material with a core-shell structure can be generated.

[0067] The copper-manganese bimetallic oxide positive electrode material of the present application has high specific capacity and good charge-discharge cycle stability, and can give the positive electrode stable charge-discharge cycle performance. It can be used to prepare the positive electrode of an aqueous zinc ion secondary battery and is used in an aqueous zinc ion secondary battery.

[0068] The present application also provides an aqueous zinc ion secondary battery positive electrode, including a current collector and a positive electrode material coated on the current collector. Among them, the current collector can be a current collector commonly used in lithium batteries, such as a stainless steel current collector, a copper current collector or an aluminum current collector, and this application does not make special restrictions; the positive electrode material is a mixture of the above-mentioned copper-manganese bimetallic oxide positive electrode material, a conductive agent and a binder; wherein the conductive agent is mainly used to improve the conductivity of the electrode material, and there is no special restriction, as long as it has conductivity without causing chemical changes. In the embodiment of the present application, the conductive agent can be selected from conductive carbon black, and the binder can be selected from polyvinylidene fluoride adhesive.

[0069] The present application provides an aqueous zinc ion secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises the above copper-manganese bimetallic oxide positive electrode material; the negative electrode is a zinc foil, the electrolyte is a ZnSO4 aqueous solution with a molar concentration of 2 M and contains 0.1 M MnSO4; the separator is a separator commonly used in zinc ion batteries, and the present application does not impose any special restrictions. The aqueous zinc ion secondary battery of the present application has a high rate capacity and good charge and discharge cycle performance.

[0070] The present application is further described below by way of examples.

[0071] Example 1

[0072] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 9:1, comprising:

[0073] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0074] Step S2, 4.5 mmol of Cu2O, 0.64 mmol of MnSO4·H2O and 0.4 mmol of KMnO4 were added to 30 mL of deionized water, and after sufficient stirring, the solution was transferred to a hydrothermal kettle and reacted in a 160 °C constant temperature drying oven for 12 h. The reaction solution was filtered to collect the solid phase product, washed with deionized water, filtered, and vacuum dried at 60 °C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.75 O@MnO2(9:1).

[0075] Example 2

[0076] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 8:2, comprising:

[0077] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0078] Step S2, 4 mmol of Cu2O, 1.28 mmol of MnSO4·H2O and 0.8 mmol of KMnO4 were added to 30 mL of deionized water, and after sufficient stirring, the solution was transferred to a hydrothermal kettle and reacted in a constant temperature drying oven at 160°C for 12 h. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain a core-shell structured copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.74 O@MnO2(8:2).

[0079] Example 3

[0080] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 7:3, comprising:

[0081] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0082] Step S2, 3.5 mmol of Cu2O, 1.92 mmol of MnSO4·H2O and 1.2 mmol of KMnO4 were added to 30 mL of deionized water, and after sufficient stirring, the solution was transferred to a hydrothermal kettle and reacted in a constant temperature drying oven at 160°C for 12 h. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.72 O@MnO2(7:3).

[0083] Example 4

[0084] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 6:4, comprising:

[0085] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0086] Step S2, 3 mmol of Cu2O, 2.56 mmol of MnSO4·H2O and 1.6 mmol of KMnO4 were added to 30 mL of deionized water, and after sufficient stirring, the solution was transferred to a hydrothermal kettle and reacted in a constant temperature drying oven at 160°C for 12 h. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.71 O@MnO2(6:4).

[0087] Example 5

[0088] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 5:5, comprising:

[0089] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0090] Step S2, add 2.5 mmol of Cu2O, 3.2 mmol of MnSO4·H2O and 2 mmol of KMnO4 into 30 mL of deionized water, stir thoroughly, transfer the solution to a hydrothermal kettle, and react in a 160°C constant temperature drying oven for 12 h. The reaction solution is filtered to collect the solid phase product, washed with deionized water, filtered, and vacuum dried at 60°C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.68 O@MnO2(5:5).

[0091] Example 6

[0092] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 4:6, comprising:

[0093] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0094] Step S2, add 2 mmol of Cu2O, 3.84 mmol of MnSO4·H2O and 2.4 mmol of KMnO4 into 30 mL of deionized water, stir thoroughly, transfer the solution to a hydrothermal kettle, and react in a 160°C constant temperature drying oven for 12 h. The reaction solution is filtered to collect the solid phase product, washed with deionized water, filtered, and vacuum dried at 60°C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.66 O@MnO2(4:6).

[0095] Example 7

[0096] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 3:7, comprising:

[0097] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0098] Step S2, add 1.5 mmol of Cu2O, 4.48 mmol of MnSO4·H2O and 2.8 mmol of KMnO4 into 30 mL of deionized water, stir thoroughly, transfer the solution into a hydrothermal kettle, and react in a 160°C constant temperature drying oven for 12 h. The reaction solution is filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.65 O@MnO2(3:7).

[0099] Example 8

[0100] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 2:8, comprising:

[0101] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0102] Step S2, add 1 mmol of Cu2O, 5.12 mmol of MnSO4·H2O and 3.2 mmol of KMnO4 into 30 mL of deionized water, stir thoroughly, transfer the solution to a hydrothermal kettle, and react in a 160°C constant temperature drying oven for 12 h. The reaction solution is filtered to collect the solid phase product, washed with deionized water, filtered, and vacuum dried at 60°C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.64 O@MnO2(2:8).

[0103] Example 9

[0104] This embodiment provides a method for preparing a copper-manganese bimetallic oxide positive electrode material with a Cu / Mn ratio of 1:9, comprising:

[0105] Step S1, 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain the precursor Cu2O.

[0106] Step S2, 0.5 mmol of Cu2O, 5.76 mmol of MnSO4·H2O and 3.6 mmol of KMnO4 were added to 30 mL of deionized water, and after sufficient stirring, the solution was transferred to a hydrothermal kettle and reacted in a constant temperature drying oven at 160°C for 12 h. The reaction solution was filtered to collect the solid phase product, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain a core-shell structure copper-manganese bimetallic oxide positive electrode material, recorded as Cu 1.61 O@MnO2(1:9).

[0107] Comparative Example 1

[0108] 2.1 mmol of Cu(CH3COO)2, 2 mmol of PVP and 0.74 mmol of NaBH4 were dissolved in 25 mL of DMF, dispersed evenly by ultrasonication, and reacted in an oil bath at 80°C for 30 min. The solid phase product was collected by filtration, washed and filtered with deionized water, and then vacuum dried at 60°C for 12 h to obtain Cu2O.

[0109] Comparative Example 2

[0110] 3.2 mmol of MnSO4·H2O and 2 mmol of KMnO4 were added to 30 mL of deionized water, and after sufficient stirring, the solution was transferred to a hydrothermal kettle and reacted in a constant temperature drying oven at 160°C for 12 h. After washing with deionized water and filtering, it was vacuum dried at 60°C for 12 h to obtain MnO2.

[0111] The positive electrode materials of Examples 1-9 and Comparative Examples 1-2 are used to prepare positive electrodes, and the specific method is as follows:

[0112] The above positive electrode materials were mixed with carbon black and polyvinylidene fluoride binder in a mass ratio of 7:2:1, and then appropriate N-methylpyrrolidone was added to grind and mix until a fine slurry was formed. The obtained slurry mixture was coated on the surface of the stainless steel mesh current collector and dried in an oven at 60°C for 12 h to prepare a positive electrode.

[0113] The above positive electrode, zinc foil negative electrode and glass fiber filter paper separator were respectively assembled into aqueous zinc ion secondary batteries, and the electrolyte was a ZnSO4 aqueous solution with a molar concentration of 2 M and containing 0.1 M MnSO4. The assembled full batteries were recorded as batteries 1-9, batteries D1 and batteries D2.

[0114] The performance test of the aqueous zinc ion secondary battery is performed, and the test results are shown in Table 1.

[0115] Table 1 Performance test data of aqueous zinc ion secondary batteries assembled with different cathode materials

[0116]

[0117] As shown in Table 1, the 2 A g of aqueous zinc ion secondary battery assembled with the copper-manganese bimetallic oxide positive electrode material prepared in this application is -1 The current density discharge specific capacity and the number of charge and discharge cycles corresponding to the capacity retention rate of 80% are much higher than those of Cu2O and MnO2. Among them, when the molar ratio of Cu to Mn in the copper-manganese bimetallic oxide positive electrode material is 4:6, such as the Cu in Example 6 1.66 O@MnO2(4:6), its 2 A g -1 The current density discharge specific capacity and the number of charge and discharge cycles when the capacity retention rate is 80% are higher.

[0118] The MnO2 of Comparative Example 2 and the Cu of Examples 1, 2, 3, 4, 5, 6, 7, 8 and 9 x Compared with O@MnO2, the difference is that Cu2O is not introduced. From the test results in Table 1, it can be seen that the introduction of Cu2O improves the conductivity of MnO2 and is beneficial to the electrolyte ion Zn 2+ It can be inserted and shuttled into the active material to promote the kinetics of electrochemical reactions. On the other hand, Cu2O is electrochemically active and can provide additional capacity, further improving the discharge specific capacity of the positive electrode material.

[0119] The copper-manganese bimetallic oxide positive electrode material Cu of Example 6 1.66 The electrodes prepared by O@MnO2(4:6) were assembled into a full battery, namely Battery 6, and the electrochemical performance test results were as follows:

[0120] Figure 1 is the cyclic voltammetry curve of battery 6, from Figure 1 It can be seen that the reduction peaks of battery 6 are 1.32 V, 1.2 V and 0.9 V, respectively, and the peak current increases successively with the increase of the scan rate.

[0121] Figure 2 is the charge and discharge curve of battery 6, from Figure 2It can be seen that the discharge platforms of battery 6 are around 1.42 V, 1.3 V and 1.1 V, respectively, and the polarization voltage is only 0.29 V. The current density is 0.5 A g -1 , 1A g -1 , 2 A g -1 , 3Ag -1 、 4Ag -1 and 5 A g -1 The corresponding discharge capacity is 215 mAh g -1 , 189 mAh g -1 、157 mAh g -1 , 136mAh g -1 , 121 mAh g -1 and 104 mAh g -1 .

[0122] Take the copper-manganese bimetallic oxide positive electrode material Cu of Example 6 1.66 The full battery assembled with electrodes prepared with O@MnO2(4:6) (battery 6) and the full battery assembled with electrodes prepared with Cu2O and MnO2 positive electrode materials (battery D1 and battery D2) were tested for rate capacity and charge-discharge cycle performance. The results are as follows: Figure 3 and Figure 4 shown.

[0123] Figure 3 Figure 2 is the rate capacity and coulomb efficiency test graph of battery 6, battery D1 and battery D2, where the blue dot is the coulomb efficiency value of battery 6. Figure 3 It can be seen that the current density is 0.5 A g -1 , 1A g -1 , 2 A g -1 , 3Ag -1 , 4Ag -1 and 5 A g -1 When the discharge rate capacity of battery 6 is 2215 mAh g -1 , 189 mAh g -1 、157 mAh g -1 、136 mAh g -1 , 121 mAh g -1 and 104 mAh g -1 , the coulombic efficiency reaches 99%; and the corresponding rate capacity of battery D1 is 193.1 mAh g -1 , 129.2 mAh g -1 、77.6 mAh g -1 、56.1 mAh g -1, 41.7 mAh g -1 and 34.3 mAh g -1 ; The corresponding rate capacities of battery D2 are 183.1 mAh g -1 、134.3 mAh g -1 、66.6 mAh g -1 , 40.4 mAh g -1 , 26.1 mAh g -1 and 18.1 mAh g -1 The rate capacity of Battery 6 is significantly improved.

[0124] Figure 4 The figure shows the charge-discharge cycle performance and coulomb efficiency test of battery 6, battery D1 and battery D2, where the blue dots are the coulomb efficiency values ​​of battery 6. Figure 4 It can be seen that battery 6 has a capacity of 2 A g -1 After 3200 cycles of charge and discharge at current density, the capacity retention rate reached 75% and the coulomb efficiency was 99%. -1 After 1400 cycles of charge and discharge at the current density, the capacity is only 10.1 mAh g -1 . Battery D2 has a capacity of 2 A g -1 After 1500 cycles of current density charge and discharge, the capacity retention rate is only 52%. The full battery capacity and cycle life of battery 6 are significantly higher than those of battery D1 and battery D2.

[0125] Figure 5 Cu 1.66 SEM test images of O@MnO2(4:6), Cu2O, and MnO2. Figure 5 In Figure a, it can be observed that MnO2 is composed of vertically arranged nanosheets, and the size of the nanosheets is less than 1 µm. Figure 5 As can be seen in Figure b, Cu2O is composed of uniformly sized nanospheres, with a particle size in the nanometer range. Figure 5 The c figure is Cu 1.66 From the SEM image of O@MnO2(4:6), it can be observed that there are open gaps between adjacent nanosheets, which provide transmission channels for various ions, effectively accelerate ion migration, and promote ion diffusion dynamics. Figure 5 Figures d, e, f, g and h are Cu 1.66 The element distribution diagram of O@MnO2(4:6) composite material shows the distribution of Mn, Cu and O in Cu 1.66 O@MnO2(4:6) is evenly distributed.

[0126] Figure 6 Cu 1.66TEM test image of O@MnO2(4:6). Figure 6 In Figures a and b, it can be observed that ultrathin MnO2 nanosheets are vertically arranged on the Cu2O surface, which is consistent with the results of SEM images, indicating that the core-shell structure of Cu 1.66 O@MnO2(4:6) composite material was successfully prepared. Figure 6 The c figure is Cu 1.66 In the HRTEM image of O@MnO2(4:6), a crystal plane spacing of 0.68 nm was measured, corresponding to the (001) crystal plane of δ-MnO2. Figure 6 Figures d, e, f, g and h are Cu 1.66 Element distribution diagram of O@MnO2(4:6), showing that Mn, Cu and O elements are evenly distributed in Cu 1.66 O@MnO2(4:6) composite materials.

[0127] Figure 7 Cu 1.66 XRD patterns of O@MnO2(4:6), Cu2O, and MnO2. It can be observed that the diffraction peaks of Cu2O appear at 36.4°, 42.3°, 61.3°, and 73.5°, corresponding to the (111), (200), (220), and (311) crystal planes of Cu2O (JCPDF: 05–0667), respectively. The diffraction peaks of MnO2 at 12.2°, 26.5°, 36.6°, and 65.6° correspond to the (001), (002), (-111), and (-312) crystal planes of δ-MnO2 (JCPDF: 80–1098), respectively. 1.66 The diffraction peaks of O@MnO2(4:6) at 12.2°, 36.6° and 65.6° correspond to the (001), (-111) and (-312) crystal planes of δ-MnO2 (JCPDF: 80–1098), respectively. The test results show that MnO2 is generated on the Cu2O surface.

[0128] Figure 8 Cu 1.66 XPS graphs of O@MnO2(4:6), Cu2O, and MnO2. Figure 8 a in the equation is Cu 1.66 The full spectrum of O@MnO2(4:6) shows that in Cu 1.66 The presence of Mn 2p, O 1s, and Cu 2p in O@MnO2(4:6) demonstrates the successful composite of MnO2 and Cu2O.

[0129] The high-resolution spectrum of O 1s is shown in Figure 8 As shown in b, Cu 1.66The three characteristic peaks of O@MnO2(4:6) can be attributed to Mn-O (528.8 eV), Cu-O (529.6 eV) and OH (531.2 eV), respectively. Figure 8 c is Cu 1.66 High-resolution spectra of Mn 2p of O@MnO2(4:6) and MnO2, Cu 1.66 O@MnO2(4:6) shows two characteristic peaks at 653.1 and 642.3 eV, corresponding to Mn 2p 1 / 2 and Mn 2p 3 / 2 The difference between the two peaks is 10.8 eV. 3+ (641.2eV and 652.5eV) and Mn 4+ (642.7 eV and 653.7 eV). Figure 8 In the high-resolution spectrum of Cu 2p in d, the characteristic peaks at binding energies of 953.7 and 932.9 eV are attributed to Cu + 2p 1 / 2 and Cu + 2p 3 / 2 orbital peak. Among them, Cu 2+ This is because the surface of Cu2O is oxidized due to long-term exposure to air.

[0130] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A copper-manganese bimetallic oxide zinc ion battery positive electrode material, characterized in that: It is a core-shell structure, with MnO2 nanosheets grown in situ on Cu x O microsphere surface, forming Cu x O core and the Cu coated x O core MnO2 shell; wherein 1<x<2; In the copper-manganese bimetallic oxide zinc ion battery positive electrode material, the molar ratio of Cu to Mn is (9:1) to (1:9); The preparation method of the copper-manganese bimetallic oxide zinc ion battery positive electrode material comprises: S1, dissolving copper salt, surfactant and reducing agent in a solvent, mixing them evenly and then performing a solvothermal reaction, collecting the solid phase product in the reaction solution, washing and drying, and obtaining a precursor Cu2O; S2, adding the precursors Cu2O, manganese salt and KMnO4 into deionized water for hydrothermal reaction, collecting the solid phase product in the reaction solution, washing and drying, and obtaining a core-shell structured copper-manganese bimetallic oxide zinc ion battery positive electrode material; The ratio of the molar number of Cu in the precursor Cu2O to the sum of the molar number of Mn in the manganese salt and KMnO4 is (9:1)~(1:9); The ratio of the molar number of Mn in the manganese salt to the molar number of Mn in KMnO4 is 1.6:

1.

2. The copper-manganese bimetallic oxide zinc ion battery positive electrode material according to claim 1, characterized in that: The molar ratio of copper salt, surfactant and reducing agent is 2.1:2:0.

74.

3. The copper-manganese bimetallic oxide zinc ion battery positive electrode material according to claim 1, characterized in that: In step S1, the temperature of the solvothermal reaction is 70°C to 90°C; In step S2, the temperature of the hydrothermal reaction is 140°C to 160°C, and the reaction time is 10 to 14 h.

4. The copper-manganese bimetallic oxide zinc ion battery positive electrode material according to claim 1, characterized in that: The copper salt is at least one of copper sulfate, copper acetate or copper chloride; The surfactant is at least one of polyvinyl pyrrolidone, sodium lauryl sulfate or hexadecyl trimethyl ammonium bromide; The reducing agent is sodium borohydride or hydrazine hydrate; The manganese salt is at least one of manganese sulfate, manganese nitrate, manganese carbonate or manganese chloride; The solvent is dimethylformamide.

5. Application of the copper-manganese bimetallic oxide zinc ion battery positive electrode material according to any one of claims 1 to 4 in zinc ion batteries.

6. A positive electrode for an aqueous zinc ion secondary battery, characterized in that: It includes a current collector and a positive electrode material coated on the current collector; The positive electrode material is formed by mixing the copper-manganese bimetallic oxide zinc ion battery positive electrode material according to claim 1, a conductive agent and a binder.

7. An aqueous zinc ion secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode comprises the copper-manganese bimetallic oxide zinc ion battery positive electrode material according to claim 1.

Citation Information

Patent Citations

  • Preparation method of manganese dioxide rechargeable aqueous zinc ion battery positive electrode material coated by metal oxide

    CN110265649A

  • Preparation method and application of high-stability copper intercalation manganese dioxide electrode material

    CN113410443A